Cholinesterase research outreach project (CROP): point of care cholinesterase measurement in an Australian agricultural community - Jacqueline Cotton; John Edwards; Muhammad Aziz Rahman; Susan Brumby (BMC, 2018)
Abstract Background Australian farmers are routinely exposed to a wide variety of agrichemicals, including herbicides and insecticides. Organophosphate (OP) insecticides are widely used for agricultural production, horticulture and animal husbandry practices. Symptoms of OP toxicity are the results of inhibition of the enzyme acetylcholinesterase (AChE) which is found in many types of conducting tissue in human bodies such as nerve and muscle, central and peripheral tissues, motor and sensory fibres. Cholinesterase can be measured in red blood cells/erythrocytes (AChE) and plasma (PChE). This study aims to explore integration of AChE monitoring into routine health checks for those at risk and also to examine any association between AChE activity and agrichemical use in a Victorian farming community in Australia. Methods This was a prospective cohort study, where farmers and non-famers were compared on the levels of AChE at four time points of baseline, 3-4 weeks, 6-weeks and at 9-weeks. Study participants (N = 55) were residents from South West Victoria, aged between 18 and 75 years, spoke English, and had not had a previous known acute chemical accident. A total of 41 farming (had been farming for more than 5 years) and a convenience sample of 14 non-farming individuals met the inclusion criteria. Testing of AChE was repeated for all participants with a maximum of three times over 10 weeks. Results The integration of AChE monitoring was very well accepted by all participants. There was no significant difference in average AChE activity between farming and non-farming participants (one-way ANOVA p > 0.05) in this study. There was no significant difference between personal use of agricultural chemicals on farm and the levels of AChE at baseline (measurement 1) or any of the follow up periods (p > 0.05). However, the mean activity of AChE was significantly lower within follow up periods [F (2.633, 139.539) = 14.967, p < 0.001]. There was a significant reduction of AChE between the follow up at 3-weeks and 6-weeks period (p = 0.015). Conclusions The routine monitoring of AChE may allow for early recognition of chronic low-level exposure to OPs when they are used by farmers, provided a reasonable estimate of baseline AChE is available. This work provides an evidence for recommending the integration of AChE monitoring into point of care (POC) procedures in rural health clinics and quantifying pesticide exposure and personal protection both on the farm and in the home. Farmer engagement is crucial to the successful integration of AChE monitoring into rural health clinics in Australia. Trial registration ACTRN12613001256763.